Measurement of Supermarket Service Quality by Applying Simple Content Analysis on Tweets - Anandianto, Rahadian; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2012)
Competition in the retail industry means that any company  trying  to attract  consumers  to buy  products  in stores with the attention to the retail marketing mix. In addition to competitive  factors,  the number  of consumer  and public complaints  about retail marketing mix noted for improve quality of  care.  Social  media  as  a  two-way  communication   between  a brand with consumers and public is the right analysis tool for use to understanding  it. So, the purpose of this study was to evaluate the retail services in Bandung  by using criteria based on service marketing  mix  of  consumer  and  public  opinion  through  social media.   To  understand   of  complaints,   researcher   use  content analysis    to   identification    the   needs    of   consumer    through sentiment.  As a new tool analysis, Twitter can be used to explore service quality of retail. The main analysis  is see the advantages and   disadvantages    of   marketing   mix   in   serving   consumer through  the division  between  the marketing  mix with a number of  conversations   for   each   sentiment.   The   smaller   the   value indicates the most important marketing mix for repair. After run the analysis,  the general  weaknesses  of retail are price, process, and people. All weaknesses in each retail must consider for management to increase satisfaction and loyalty of consumers. Keywords:  marketing  mix, retail service,  content  analysis,  Twitter, conversation